Pengaruh Penerapan Metode Menulis Berantai terhadap Peningkatan Kemampuan Menulis Karangan Siswa SDN Mannuruki Kota Makassar: The Effect of Implementation of the Chain Writing Method on Improving the Writing Ability of Students at SDN Mannuruki, Makassar City - Saharuddin, Saharuddin; Azwar, Azwar (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to: (1) find out the description of the improvement in essay writing skills in the Indonesian language subject of fifth grade students at SDN Mannuruki Makassar City; (2) to determine the effect of applying the estafet writing method to increasing the ability to write essays in the Indonesian subject of fifth grade students at SDN Mannuruki Makassar City. This research is an experimental research with a quantitative research approach using the Paired Samples T-Test analysis technique. The results of this study indicate that: (1) after being given treatment in the experimental group, student scores experienced a significant increase. While the results of the post-test in the control group which were not given treatment or used conventional methods, also experienced a significant increase. However, the average obtained in the class that was given the treatment (experiment) or the class that used the chain writing method was higher; (2) there is a positive effect of applying the chain writing method to improving the writing skills of fifth grade students at SDN Mannuruki Makassar City. Therefore, teachers are advised to use the serial writing method in Indonesian subjects as an innovation in teaching and learning activities so that students do not feel bored in the learning process and the material presented can be conveyed and well received.